"Respondabilidad" En Las Instituciones De Educación Superior (2012)
This article is oriented to the study of "respondability" in Institutions of Higher Education, particularly in Colombia’s education system. For this purpose, and resorting to the method of document analysis, four elements of development were divided in: "Respondability", Responsibility, "Respondability" in higher education, and conduction of "Respondability" in higher education institutions in Colombia, to achieve a conception of its postulates in each of them, and finally, from a critical analysis to account for some efforts done in this country within the scope of "respondability". It was possible to match the perspective of different authors of the concept of "respondability", with the approaches of Manno, Mcmeekin, Puryear, Winkler and Winters (2006), for which at the end of the document, a set of actions is promoted for higher education institutions as a way of working immersed in this new mechanism called "respondability". The study concludes that in Colombia, public institutions of higher education show efforts toward the design and development of beneficial academic programs for students, which have their respective monitoring and tracking mechanisms, thus, engaging institutions into accountability